THE LESUNG MUSIC IN THE VILLAGE OF LEDOK BLORA REGENCY - Suharto, S.; Aesijah, Siti (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2014)
This research aims to identify in order to preserve traditional art lesung music in Blora Regency. This research use ethnomusicology approach. The subject of research is Blora people who still play lesung music as an expression of social and cultural activities in the community. The setting of the research took place in Ledok village. The technique of collecting data is observation and interview. The validity of data uses triangulation techniques. The data collected was analyzed with interactive type of Miles and Huberman. The result of research shows that the form of lesung music uses simple rhythms with elements of rhythm, melody, and harmony. Harmony in music is from the rhythmic beats of polyphonic arranged. This kind of music at first had any functions for the purposes of ritual, entertainment, welcoming guests, harvesting/offerings, a sign of the eclipse. Today, it serves as a means of musical entertainment at the village greeting, social interaction, and tourism. There is a shift of function due to the mindset of the people and the swift technology advances. Lesung music needs a modification in its presentation by adding songs and games. Another art element like dance can be added to make the show more interesting to be enjoyed.